Pengaruh Motivasi, Disiplin, Dan Fasilitas Kerja Terhadap Kinerja Pegawai: Studi Kasus Pada UPTD Puskesmas Pagerbarang, Kabupaten Tegal - Apriliyani Nur Khasanah; Setya Pramono (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This study aims to determine the partial and simultaneous effects of motivation, discipline and facilities on the job performance of UPTDPagerbarang Clinic employees. This research is included in quantitative research using a sample of 87 UPTD Pagerbarang Oinic employees with saturated sampling technique. The data was processed with the SPSS 26.00 application using the multiple regression method. The results of data processing from this study show the results where the three independent variables have a significant effect on improving employee performance. The results of hypothesis testing show that motivation, discipline, and work facilities have a very significant effect on employee performance. The results of the F test show that simultaneously has a significant influence on employee performance.